THE DIFFERENCES BETWEEN PROTEIN, SELECTED VITAMINS AND SELENIUM TO MORBIDITY IN YOUNG CHILDREN - Mulyani, Erry Yudhya; Angkasa, Dudung; Elvandari, Milliyantri; Jus’at, Idrus (Universitas Muhammadiyah Semarang, 2017)
Morbidity rate in children under 3 years of age is higher among rural than urban area. Adequate intake of protein and selected vitamins suppresses the immune system to function efficiently. This cross-sectional study at Tangerang district was aimed to understand the difference in protein, selected vitamins and selenium intake to morbidity episode among young children. A total of 87 children under 3 years of age was drawn randomly from 3 selected villages. All measurement was carried out by well trained professional health personnel’s. The independent t-test and Mann-Whitney were employed to analyze the data. The youngchildren aged 7-11 month (16.1%) and 12-36 month (83.9%), weight was 9.8±2.1 (kg), height was 78.5±8.1(cm), and MUAC was 13.5±6.6 (cm). The average intake of protein, Vitamin C, Vitamin E and Selenium inchildren aged 7-11 month were 12.7±11.0 (g), 42.7±108.1 (mg), 0.8±1.2 (mg), and 0.1±0.0 (mcg), respectively. Then for the children age 12-36 month were 26.6±15.5 (g), 23.0±34.6 (mg), 2.2±1.8 (mg), and 0.3±1.4(mcg), respectively. There were no differences in protein, vitamin C, vitamin E and selenium intakes between morbidity episode among children aged 12-36 month (p≥0.05). While, there was a difference in protein intake between morbidity status in younger children (p<0.05). This study failed to find contribution of selected vitamins and selenium to morbidity status. An adequate intake of protein, selected vitamins andminerals was needed to curb the intermittent infections.Keywords: Protein, Selected Vitamins, Selenium, Morbidity, Young Children